PENGARUH SATISFACTION, PERCEIVED VALUE, DAN TRUST TERHADAP STORE LOYALTY DI CARREFOUR SURABAYA - Wijaya, Elisabeth Nancy (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
The development of retail business in Indonesia now requires companies to have the right strategy in marketing their products. Each retailer always try to give the best results to their customers in order to give satisfaction to the customer. The aim of this research is to find out: (1) the influence of satisfaction on store loyalty, (2) the influence of perceived value on store loyalty, (3) the influence of trust on store loyalty. Technical analysis of research using multiple linear regression analysis. Respondents in the research were from existing customers in Surabaya who have shopped at Carrefour Surabaya. The results showed that: (1) satisfaction influence on store loyalty, (2) perceived value influence on store loyalty, (3) trust influence on store loyalty.